DSA-FXM: Accelerated Donor-specific Flow Crossmatch Discriminating Class I and II Antibody Specifically and Only to Donor HLA for Determining True Incompatibility. Issue 4 (April 2020) - Chen, Ge; Lin, Lingling; Tyan, Dolly B.
Abstract : Background: Worldwide, a final crossmatch is the gold standard for determining compatibility between patient and donor before solid organ transplantation and preventing hyperacute rejection. In the absence of autoantibodies, an incompatible crossmatch in a sensitized patient is attributed to mismatched donor HLA. However, current physical crossmatch methods cannot distinguish reactivity to HLA from other clinically irrelevant cell surface targets nor the class of HLA if it is the target. Result interpretation is difficult or impossible when autoantibodies, alloantibodies, or therapeutic antibodies coexist. Methods: Herein, we describe a unique donor-specific flow crossmatch (DSA-FXM) that distinguishes HLA class I or II donor-specific antibody bound to HLA antigens on the donor cell surface in their native conformation that is not impacted by rituximab, anti-thymocyte globulin (after absorption), or autoantibodies. It is HLA specific. Results: We compared the results of single-antigen antibody testing, autoreactive and alloreactive flow cytometry crossmatches (FXM) using traditional FXM and our DSA-FXM method from 94 patients (enriched for auto+/allo+ pairs; n = 64) against 110 donors (338 tests) and show that, in our cohort, positive traditional FXM results are not directed to donor HLA 60.25% of the time and negative traditional FXM results are missing HLA donor-specific antibody 36.2% of the time based on the DSA-FXM. Conclusions: We demonstrate that the DSA-FXM is able to define categorically distinct and clinically important HLA antibody profiles in half the time required for the standard FXM, potentially shortening cold ischemia time and providing clinicians with unambiguous essential information regarding HLA compatibility when time is critical. Abstract : Supplemental Digital Content is available in the text.